2012
DOI: 10.1103/physrevlett.108.035502
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hybridization Governs Molecular Electrical Doping

Abstract: Current models for molecular electrical doping of organic semiconductors are found to be at odds with other well-established concepts in that field, like polaron formation. Addressing these inconsistencies for prototypical systems, we present experimental and theoretical evidence for intermolecular hybridization of organic semiconductor and dopant frontier molecular orbitals. Common doping-related observations are attributed to this phenomenon, and controlling the degree of hybridization emerges as a strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
259
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(279 citation statements)
references
References 33 publications
19
259
1
Order By: Relevance
“…12 In many cases, however, a redox model is used wherein a single electron is transferred from P3HT to F4TCNQ leading the formation of charge carriers in the form of either polarons or bipolarons. Fortunately, regardless of which model is chosen, doping generally introduces absorption features in the sub-bandgap region.…”
Section: Introductionmentioning
confidence: 99%
“…12 In many cases, however, a redox model is used wherein a single electron is transferred from P3HT to F4TCNQ leading the formation of charge carriers in the form of either polarons or bipolarons. Fortunately, regardless of which model is chosen, doping generally introduces absorption features in the sub-bandgap region.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Here, the aim of our study is to explore the formation mechanism of the molecule-doped conjugated polymer/electrode interface by photoemission spectroscopy, and conclusively establish its universal energy level alignment. Analysis is carried out under the assumption that doping leads to charge transfer and not hybridization, as recent investigations by Pingel et al [37] revealed an ionized dopant and free charge formation in F4TCNQ doped polymer rr-P3HT and ruled out intermolecular hybridization [38] in this system. Considering that the doping efficiency is significantly dependent on the doping concentration and there is a threshold above which doping significantly affects electrical conductivity corresponding to a concentration where a sufficient percentage of the bound charge pairs (~5%) overcome the Coulomb dissociation barrier into free charges, [18,37] we chose doping concentrations of 3:1000, 3:100, 1:10 and 2:10 w/w (dopant to polymer weight ratio) in F4TCNQ:rr-P3HT, to span the range of low-intermediate-high doping (Fig.1c).…”
Section: Introductionmentioning
confidence: 99%
“…However, interactions between the dopant and the host material-either strong coulombic interactions between ions or through overlap of dopant and frontier molecular orbitalscan also result in trapping of charge carriers. [17][18][19] While the insertion of ionized dopants is likely to disrupt molecular order, and is known to affect the density of states of the host, 11 ultra-low doping of the host matrix is expected to minimize dopant-induced defects and achieve passivation of deep trap states, experimentally demonstrated by a significant increase in electrical conductivity with a systematic increase in doping concentration. Olthof et al showed that conductivity, electron mobility, and activation energy of C 60 films n-doped with a dimeric organometallic reductant, processed via co-evaporation in UHV, exhibited two clear regimes of dependence on dopant concentration, and attributed these two regimes to (i) trap-filling and (ii) mostly trap-filled charge transport.…”
mentioning
confidence: 99%
“…24,25 The concentration of P(NDI 2 OD-T 2 ) in toluene was kept constant at 10 mg/ml throughout all measurements to achieve uniform film thicknesses across devices. The dopant solution was added to the host solution in very small amounts, ranging from 7.8 Â 10 À5 to 7.8 Â 10 À3 molar ratio (MR), which correspond to doping densities of 6 Â 10 16 to 6 Â 10 18 26,27 and previous experiments on the closely related rhodocene dimer/ P(NDI 2 OD-T 2 ) system 20,21 indicate the feasibility of the reaction, as shown in Fig. 1.…”
mentioning
confidence: 99%